Detection of a Novel Bovine Astrovirus in a Cow with Encephalitis. Issue 3 (7th March 2016) - Schlottau, K.; Schulze, C.; Bilk, S.; Hanke, D.; Höper, D.; Beer, M.; Hoffmann, B.
Summary: Encephalitis can be caused by several infectious agents, including bacteria, fungi, parasites and viruses. In many cases, the causative agent cannot be identified, because the pathogens are unknown or detection methods are not routinely available. In our case, a 15‐month‐old cow developed central nervous disorders and died within 6 days after the onset of clinical signs. The histopathology revealed an acute encephalitis, predominantly in the brain stem, and a ganglionitis of the trigeminal ganglion with massive neuronal necroses in both the brain and the ganglion. However, a relevant panel of bacterial and viral infections of cattle could be routinely excluded. Therefore, a brain sample from the cow was analysed using a metagenomics approach with next‐generation sequencing. A novel bovine astrovirus (BoAstV‐BH89/14) could be identified using the analysis pipeline RIEMS, and the finding could be confirmed with a specific BoAstV RT‐qPCR. The genome of the bovine astrovirus (BoAstV), belonging to the family Astroviridae in the genus Mamastrovirus, has a length of 6478 bp. Sequence identities between 71% to a sheep astrovirus and 69% to two recently described bovine astroviruses from the USA and Switzerland were ascertained. The latter were also connected to encephalitis cases in cattle. Like these, the new virus described here was detected in different brain sections using the specific BoAstV RT‐qPCR and fluorescent in situ hybridization. In conclusion, while astroviruses so far were mainly found in relation to gastroenteritis in animals and humans, recently detected astrovirus infections were also related to encephalitis.